Pembuatan Bioetanol Dari Kulit Nanas Dengan Metodeliquid State Fermentation (LSF) Dengan Variasi Waktu Dan Konsentrasi Inokulum - Deasy Rahmayuni; Chairul Chairul; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The world consumption of bioethanol for a variety of uses has increased very significantly in recent years. Pineapple skin is one of the potential materials to be processed into bioethanol. Availability of food waste material containing glucose as the skin is still fairly abundant pineapple and its utilization is limited only used for fertilizer and animal feed, so it is necessary for utilization of that adds value as well as a fairly high sugar content (13.65 % reducing sugar) makes the skin of pineapple has the potential to be processed into bioethanol. Through the process of fermentation using Zymomonas mobilis, glucose is converted into ethanol and carbon dioxide. Preparation of starter inoculum carried by Zymomonas Mobilis process. Fermentation takes place in batches with a volume of 1 liter of fermentation medium, fermentation time variation of pH 5 2 , 4 , 6 and 8 days and inoculum concentration variation of 5 , 10 and 15 % (v / v). Stirring speed of 200 rpm and temperature of fermentation at room temperature (25o – 30oC). Bioethanol concentration was analyzed by using gas Chromathography Mass Spectroscopy. The process of optimum fermentation conditions shown in inoculum concentration of 10% v / v and 4 days fermentation time. The concentration of bioethanol obtained under these conditions is 43.10 % (v / v) or 23.75 g / ml.Keyword :Bioethanol, Pineapple Peel, Fermentation, Zymomonas mobilis, Liquid State Fermentation